Analisis Pengelolaan Infak di Masjid Nurul Falah Kelurahan Toro Kabupaten Bone: Tinjauan Transparansi dan Akuntabilitas - Misnawati, Misnawati; Ramadhani, Sri; Hasbi, Hartas (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This research aims to analyze donations management practices at the Nurul Falah Mosque, Toro Village, Bone Regency with a focus on the level of transparency and accountability. This research uses a descriptive qualitative method by collecting data using in-depth interviews, observations and also documentation with the mosque management. The research results show that the management of donations at the Nurul Falah Mosque has a financial recording and reporting mechanism, but it still does not meet standards but is quite good in terms of transparency and accountability. This research indicates several challenges, including the limitations of a comprehensive reporting system, resulting in the need for more structured financial documentation, improved periodic reporting mechanisms, and a more open communication strategy. This research provides an important contribution in understanding donations management practices at the local level and offers strategies to increase public confidence in mosque financial management. It is hoped that this research can become a reference for mosque managers in developing financial governance that prioritizes transparency and accountability.